2013
DOI: 10.1097/coc.0b013e3182438c71
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Outcomes of Small Cell Carcinoma of the Bladder Using the Surveillance, Epidemiology, and End Results Database

Abstract: Small cell carcinoma of the bladder is a rare but aggressive malignancy with poor OS. For those who present without widespread metastatic disease, treatment with either cystectomy or radiation appears to improve survival. Further prospective studies are needed to determine the best approach for treatment of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…63 For patients unable to undergo cystectomy, combined chemoradiotherapy has been proposed as an alternative with fairly equivalent outcomes based on small retrospective cohorts with short follow-up. 64,65 Because of the need for systemic treatment for small cell carcinoma of the bladder, intravesical therapy for NMI small disease conceptually is inappropriate. Although this Variant Histology Bladder Cancer has never been officially reported, we advocate primary chemotherapy with a small cell-specific regimen (ie, cisplatin with etoposide) followed by surgical extirpation as the mainstay of treatment for any degree of small cell carcinoma at any stage.…”
Section: Small Cell Carcinomamentioning
confidence: 99%
“…63 For patients unable to undergo cystectomy, combined chemoradiotherapy has been proposed as an alternative with fairly equivalent outcomes based on small retrospective cohorts with short follow-up. 64,65 Because of the need for systemic treatment for small cell carcinoma of the bladder, intravesical therapy for NMI small disease conceptually is inappropriate. Although this Variant Histology Bladder Cancer has never been officially reported, we advocate primary chemotherapy with a small cell-specific regimen (ie, cisplatin with etoposide) followed by surgical extirpation as the mainstay of treatment for any degree of small cell carcinoma at any stage.…”
Section: Small Cell Carcinomamentioning
confidence: 99%
“…Literature review identified 43 retrospective series and case reports, the majority being quite small (range: 1-663 patients). 68 The only prospective studies were a non-randomized phase II study 31 and a single-centre study of 25 cases treated in a fashion analogous to SCLC. 28 The National Cancer Care Network (NCCN) 69 was the only identified guideline which included SCCB.…”
Section: Treatmentmentioning
confidence: 99%
“…In the previously described SEER data, 68 patients with metastatic disease at diagnosis had a median survival of 5 months (95% CI, 3.7-6.3). In addition, Ismaili and colleagues reported that patients with recurrent and metastatic SCCB had a median overall survival of 7.6 months.…”
Section: Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations